HISTORY EDUCATION IN CURRICULUM 2013: A NEW APPROACH TO TEACHING HISTORY - Hasan, Said Hamid (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2013)
There has been so many findings and thoughts indicating that teaching history is dominated by what teachers tell of what happened in the past as it is written in the textbooks or reference books. Students listen, read, and memorize the narration and the more details the student could memorize the higher mark she/he will get. The plan for teaching history, syllabus or lesson plan, shows a high level of consistency amongst the learning objectives, teaching processes, and assessment of student learning outcomes. Memorize of historical facts and the reproduction of historical narratives as indication of student’s understanding of historical events, the transmission of information from teacher to student to realize the objectives, and the use of pencil and paper test to assess student level of achievement are the common practices in school from primary to secondary education. It would be no surprise if teaching history at the higher level of education would follow the same path. Public still consider a good scholar or historian in this case, is measured by the amount of knowledge she/he can memorize and she/he should be able to answer some many questions of the facts of historical events. In fact, there is no question of how many a student has in her/his memory apart from what is questioned.